(untitled) (Ameghiniana, 2013)
Borings on subfossil and modern specimens of Hialella salida (Sowcrby) and Tawcra gayi (Hupé), epifaunal and semi-infaunal specics respectively, are described. Two borehole types are recognized. One type is present in the two species and its morphology varies according to the prey shell morphology. The other type occassionally appears on Tawcra goyi shells. In both cases the holes are attributed to muricids. In the two bivalves considered there is not a prey size selection, neither a correlation between the prey size (valve length) and the predator size (bore diameter) or between the prey sizc and the site of boring. Preferred areas of drilling are recognized. This site selection appears to be related to the morphology and life habits of the prey-predator complex. The presence of incomplete boreholes in Tawera gayi is an indcx of the unsuccessful predation on the species. No differences between subfossil and modern specimens of Tawera gayi reflecis a (palco) ecological similarity between the fauna of the two geological ages.